EVALUATION OF ANTIBACTERIAL ACTIVITY OF NICKEL OXIDE NANOPARTICLES AGAINST ESCHERICHIA COLI - H. O. Ahmed; L. A. Yaaqoob (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study’s goals are to use pyocyanin pigment produced by the clinical isolate Pseudomonas aeruginosa as a reducing and stabilizing agent for nickel oxide nanoparticles (NiO NPs) and their use it antibacterial agents against biofilm-producing, multidrug-resistant Escherichia coli isolated from various clinical sources. The antibiotic susceptibility test of E. Coli isolates was shown to be resistant to ceftriaxone, cotrimoxazole, piperacillin-triazole, tetracycline, and ticarcillin, while sensitive to Amikacin, Amoxicillin, Nitrofurantoin, and Imipenem. NiO NPs are synthesized by using nickel sulfate NiSO4 (10g) with a concentration of pyocyanin (10mg/10ml). The NiO NPs synthesized were characterized by various techniques such as AFM, UV-VIS, and FTIR. The result showed that the wavelength of NiO was 211nm and the average diameter of NiO was 63.59 nm, and the concentration of NiO NPs was 0.5 mg/ml, showing that the maximum inhibition zones of E.coli were 22 mm. Biosynthesis of NiO NPs using pyocyanin was shown to have promising activity as an antibacterial against the biofilm-producing E. coli.